(untitled) (Altre Modernità, 2016)
Considering audiovisual translation as both gateway and gatekeeping for the transmission of socio-cultural, ethnic, religious and moral values in wide contexts of intercultural dynamics and taking into account its being often intertwined with ideological manipulation (Díaz Cintas 2012), audiovisual products prove to be particularly suitable to illustrate the complexity of real-life multilingual realities (Bleichenbacher 2008), increasingly represented in contemporary British and American films dealing with the themes of cultural conflict, alienation and assimilation in multiethnic communities characterized by language crossing and trans-cultural awareness. In such multilingual environments, linguistic identities are constantly open to renegotiation, reconstruction and reinterpretation and code-switching plays a crucial role in the immigrant characters’ discourse practices as an entry to their cultural and linguistic memory. Starting from these assumptions, this paper aims at looking contrastively at the translation strategies of the different types of code-switching to be observed in the Italian dubbed versions of such British and American intercultural films as Bend it Like Beckham (Chadha, 2002), My Big Fat Greek Wedding (Zwick, 2002), Real Women Have Curves (Cardoso, 2003), Ae Fond Kiss (Loach, 2004), Spanglish (Brooks, 2004), Gran Torino (Eastwood, 2008), My Life in Ruins (Petrie, 2009), where the clash of cultures is mostly emphasized by the characters’ linguistic choices. The film scripts will be analysed focusing, in particular, on those cases where it is possible to recognize some sort of ideological and cultural manipulation applied in re-constructing, re-narrating and re-interpreting the characters’ multicultural identity for the Italian audience, thus possibly leading the defining ethno-cultural and linguistic features of the films’ original dialogues to be diluted to the point of neutralization (Pavesi 2005) and therefore failing to convey the translanguaging space (Wei 2011) the immigrant characters live in.